Konsep Dasar Ekonomi Pendidikan pada Tataran Suprastruktur dan Infrastruktur Politik di Indonesia - Irjus Indrawan (INNOVATIO: Journal for Religious Innovation Studies, 2019)
Education is a conscious and planned effort to create an atmosphere of learning and learning process so that students actively develop their potential. Education is a basic need factor for every human being so that efforts to educate the life of the nation, because through education efforts to improve people's welfare can be realized. The politics of education is all efforts, policies and strategies related to the problem of education. The politics of education is a general explanation or understanding determined by the highest education authority to direct ideas and determine actions with educational devices in various similarities and diversity along with the objectives and programs to realize them. The politics of education contains the policies of a country's government regarding education. The politics of education is not only in the form of written laws and regulations, but also includes other policies relating to education. The politics of education is aimed at the success of education providers that are run for the achievement of the goals of the state, because the goals of the state are the main targets in the administration of education.